2011
DOI: 10.1002/dneu.20854
|View full text |Cite
|
Sign up to set email alerts
|

Heparan sulfate proteoglycan specificity during axon pathway formation in the Drosophila embryo

Abstract: Axon guidance is influenced by the presence of heparan sulfate (HS) proteoglycans (HSPGs) on the surface of axons and growth cones (1–5). Multiple HSPGs, including Syndecans, Glypicans and Perlecans, carry the same carbohydrate polymer backbones, raising the question of how these molecules display functional specificity during nervous system development. Here we use the Drosophila central nervous system (CNS) as a model to compare the impact of eliminating Syndecan (Sdc) and/or the Glypican Dally-like (Dlp). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
(61 reference statements)
1
23
0
Order By: Relevance
“…For example, glypicans have been shown to play a role in axon guidance [310, 324], and in the formation of excitatory synapses [325, 326]. …”
Section: The Role Of Glypicans In Breast Cancer Progressionmentioning
confidence: 99%
“…For example, glypicans have been shown to play a role in axon guidance [310, 324], and in the formation of excitatory synapses [325, 326]. …”
Section: The Role Of Glypicans In Breast Cancer Progressionmentioning
confidence: 99%
“…Recent insight into the structural requirements for binding between Slits and Robo1 has revealed that the complex can be stabilized by heparan sulfate glycosaminoglycans (GAGs), which are required for functional Slit/Robo signaling in both Drosophila and vertebrate neurological development (Figure 1C) (Fukuhara et al, 2008; Hu, 2001; Hussain et al, 2006; Inatani et al, 2003; Ogata-Iwao et al, 2011; Plump et al, 2002; Schulz et al, 2011; Smart et al, 2011). There appears to be dual functions for these GAGs: first, they bind to Slit in the extracellular matrix and stabilize their interaction with Robo, and second, they act on target cells to mediate Slit/Robo signaling by serving as co-receptors.…”
Section: The Slit/robo Signaling Interaction Is Well Characterizedmentioning
confidence: 99%
“…However, it is unclear whether or not these GAGs constitute membrane bound proteoglycans. Genetic studies in Drosophila suggest that this may be the case, as the heparan sulfate proteoglycan, glypican, which is associated with the cell surface via a glycosylphosphatidylinositol (GPI) linkage, interacts with slit and regulates its distribution (Liang et al, 1999; Ronca et al, 2001; Smart et al, 2011; Zhang et al, 2004). Thus, heparan sulfate GAGs, either cell associated or present as free sugars in the extracellular matrix, concentrate and localize Slits, shaping the signaling environment by regulating their concentration and accessibility.…”
Section: The Slit/robo Signaling Interaction Is Well Characterizedmentioning
confidence: 99%
“…Further, decreasing Laminin or integrin expression enhances the axon pathfinding defects in a Slit hypomorphic allele, suggesting that the BM modulates axonal responsiveness to Slit signals (Stevens & Jacobs, 2002). Slit binding to Heparin also enhances the Slit-Robo interaction (Hussain et al, 2006), and the transmembrane HSPG Syndecan, which can function as a BM receptor (Carey, 1997), acts with Robo as a Slit co-receptor (Johnson et al, 2004; Smart et al, 2011; Steigemann, Molitor, Fellert, Jäckle, & Vorbrüggen, 2004). Whether this interaction occurs cooperatively with or independently of the BM is unclear, although Perlecan, the BM HSPG, does not appear to exhibit similar activity (Steigemann et al, 2004).…”
Section: Contributions Of the Bm To Cell-cell Signaling During Devmentioning
confidence: 99%